Evaluation of the amount of residual monomer released from different flowable composite resins - Didem Odabasi; Cigdem Guler; Didem Kucukaslan (BMC, 2024)
Abstract Today, resin materials are used in the restoration of permanent and deciduous teeth or as fissure sealants. The materials can contain different types of monomers (Bis-GMA, UDMA, TEGDMA). These monomers can be released into the oral cavity after polymerization. Residual monomers released from resin-containing restorative materials after polymerization have been reported to have negative effects on mechanical properties. The aim of our study is to evaluate the amount of residual monomers released after polymerization of different flowable composite resin materials using two different modes of LED light source. Composite disc samples (8 mm diameter/2 mm depth) prepared for each material group were polymerized using two different modes of the LED light device (Standard mode and extra power mode). HPLC (High Performance Liquid Chromatography) device was used to measure the amount of residual monomer release at 1 h, 1 day, 3 days and 7 days periods. Pairwise comparison of the differences between the materials was performed by Post-hoc test. For each residual monomer, the Kruskal Wallis test was used to analyze the difference between the materials in standard mode and the difference between the materials in extra power mode. According to the results of the study; Grandio flow flowable composite showed the highest release of TEGDMA and Bis-GMA while SDR® Flow flowable composite showed the lowest release of TEGDMA, Bis-GMA and UDMA. For all materials, the extra power mode resulted in more residual monomer release. TEGDMA and Bis-GMA release was detected in all tested flowable composites at all time periods.